Erosion Infiltration in the Management of Molar-Incisor Hypomineralization (MIH) Defects - Rym Mabrouk; Souha Yahia; Afef Oueslati; Nadia Frih (Hindawi Limited, 2020)
White spot lesions caused by enamel demineralization are frequently encountered in dental practice. Their management has always been an important issue in modern dentistry. However, the real dilemma was treating aesthetic demands with noninvasive or minimally invasive techniques preserving the natural tissues. The introduction of resin infiltration technique seems to provide an intermediary treatment modality between prevention and restorative therapy. This case report is aimed at reporting the management of MIH opacities in anterior teeth with resin infiltration technique.